METAPOLIS. TOPOI. SCENARIOS: For Urban-Rural Sustainability in Lower Saxony - Carlow, Vanessa Miriam; Abou Jaoude, Grace; Karadag, Chantal; Mumm, Olaf; Scheer, Marie; Schöning, Kristin; Zeringue, Ryan (JOVIS, 2023)
Urban and rural areas alike witness severe dynamics.Moreover, understandings of what constitutes the urban and the rural are changing, too.Metapolis conceptualizes the network of urban and rural settlements interconnected by flows of people, goods, and information.How can this Metapolis be understood and evolve in a more sustainable manner?.